Experimental and clinical combined photodynamic therapy for malignant and premalignant lesions using various types of radiation - Y. S. Romanko; I. V. Reshetov (Сибирский онкологический журнал)
The aim of the study was to present various types of radiation that can increase the effectiveness of combined photodynamic therapy (PDT) for malignant and premalignant lesions. Material and Methods. The Web of Science, Scopus, MedLine, Library, and RSCI databases were used for finding publications on this topic, mainly over the last 10 years. Of 230 sources, 64 were included in the review. Results. Photodynamic therapy is a new cancer treatment technology that has become increasingly popular in recent years. It is often an alternative method of treating cancer when there is a high risk of side effects and complications during traditional treatments such as surgery, radiation therapy and chemotherapy. PDT requires a photosensitizer, light energy, and oxygen to create reactive oxygen species that destroy cancer cells. This review examines the basic principles and mechanisms of PDT used alone and in combination with other traditional therapies. Despite the fact that PDT is an effective and non-invasive cancer treatment, it has some limitations, such as low light penetration depth, ineffective photosensitizers and tumor hypoxia. Our study examines new strategies that use other energy sources, such as infrared- and x-rays, ultrasound, as well as electric and magnetic fields, to enhance the PDT effect and overcome its limitations. Great hopes are also associated with the use of a combination of PDT and neutron capture therapy (NСT). Currently, chlorin derivatives associated with boron carriers have been developed. They can be used for both fluorescence diagnostics and PDT, as well as for NСT. The synthesized compounds have a high selectivity of accumulation in the tumor. To date, encouraging preclinical results of high efficiency of combined use of NСT and PDT have already been obtained. Conclusion. Combination with various energy sources is a key factor for further development of PDT. Future research aimed at overcoming the limitations of PDT will contribute to unlocking the full potential of this technology in clinical practice.